ANALYSIS AND APPLICATION OF CLOUD STORAGE SECURITY UTILIZATION BASED ON AS A SERVICE (IaaS) INFRASTRUCTURE SERVICE MODEL AS A DOCUMENT SHARING MEDIA DURING PANDEMI - Isra Wardanu, Fyan; Wibowo, Budi; Yuswanto, Andrie (Department of Computer Engineering, Universitas Wiralodra, 2022)
Storage via the cloud is very necessary which is carried out in this research can be used as a basis for research at PT. Indocode technology has a problem where the problem is that the process of storing and sharing data on storage media via the cloud can be used both on internal and external networks. Implementing cloud-based storage greatly simplifies the process of sharing files with employees or the board of directors to be able to filter which data can be accessed by all employees and limited needs.. The server is designed using the Owncloud application which aims to support the process of information or data transactions with commissioners, directors and employees using owncloud, so that the data transfer process no longer uses external storage from the internet or other physical storage media. In addition, the use of owncloud for enterprises is very helpful because it is easy to use and the file sharing capabilities can be adjusted according to the user's permissions and can be accessed anywhere and anytime.